Physicochemical, antioxidant and sensory properties of puffed longan-rice snack by extrusion process - P. Leawtrakoon (2018)
For the development of puffed longan-rice snack, three styles of longan; namely, fresh longan, hot air-dried longan and freeze-dried longan were used. The physicochemical properties of the three longans were analyzed. The results showed that fresh longan has the lowest values of L, a and b (P < 0.05). The total phenolic content and antioxidant activity (DPPH) of fresh longan (based on dry basis) were the highest (P < 0.05), followed by freeze-dried and hot air-dried longan, respectively. The puffed snacks were prepared from each style of longan by a single screw extruder with the longan content of 5 g per 100 g of main ingredients. The puffed snack with fresh longan showed the highest values of L and expansion ratio, but not for the a, b, bulk density and penetration force values. The water absorption index of these longan snacks was not significantly different (P=0.05). After extrusion, the total phenolic content and the antioxidant activity (DPPH) of puffed snack with hot air-dried longan were highest (P < 0.05). The sensory attributes of puffed snacks were also studied and found that the scores of appearance, colour, odor, smoothness, crispness and overall acceptance of all longan snacks were not significantly different (P=0.05). However, the scores of taste of snack with dried longans were higher than that of fresh longan (P < 0.05).